SINTESIS O-KARBOKSIMETIL KITOSAN PADA BERBAGAI KONSENTRASI NaOH DAN SUHU REAKSI SERTA APLIKASINYA SEBAGAI ANTIBAKTERI - Jaya Hardi; Nurakhirawati Nurakhirawati; Ahmad Ridhay; Musdalifah Musdalifah (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2017)
The research about the influence of NaOH concentrations and reaction temperature to O-Carboxymethyl Chitosan (O-CMC) synthesis and it is antibacterial application was done. This research intent on detect NaOH concentration and reaction temperature that resulting of O-CMC with highest of yield, solubility, and substitution degrees, and also to find out FTIR spectrum and antibacterial activity of O-CMC. The produce of O-CMC was done by using a Completely Randomized Design (CRD) with the variation of NaOH concentration of 20%, 30%, 40%, 50%, and 60%, and also reaction temperature of 20, 30, and 40oC. The result was showed that on the NaOH concentration of 60% (w/v) and temperature of 30oC was resulted highest of yield, solubility, and substitution degrees of 41.5%, 31 g/L, and 0.67, respectively. FTIR spectrum was showed that bending vibration of primary amine (-NH2) give two bands for O-CMC. The broadest inhibition area of O-CMC (1.43 cm) was showed on Salmonella sp.Keywords: chitosan, O-CMC, substitution degree, antibacterial